Assessing and rethinking the statutory scheme for derivative actions under the Companies Act 2006. Issue 1 (2nd January 2016) - Keay, Andrew
ABSTRACT: In October 2007 a statutory scheme, designed to address the issue of derivative actions, came into force. The scheme provided that shareholders wishing to continue (or commence) derivative proceedings in relation to wrongs committed against their company had to obtain the permission/leave of the court. In the subsequent eight years there have been few derivative actions instituted by shareholders and only a small percentage of actions commenced have succeeded in obtaining court permission/leave to proceed. This article undertakes an analytical review of the statutory scheme and identifies reasons why there are so few proceedings in the UK, and more broadly it examines and evaluates the derivative action scheme itself. The article considers whether the statutory scheme is too narrow and explores some changes that might be made to it in order to make it more accessible and more effective.